Histone H3 Lysine 36 Methyltransferase Whsc1 Promotes the Association of Runx2 and p300 in the Activation of Bone-Related Genes - Lee, Yu Fei (Public Library of Science, 2014)
The orchestration of histone modifiers is required to establish the epigenomic status that regulates gene expression during development. Whsc1 (Wolf-Hirschhorn Syndrome candidate 1), a histone H3 lysine 36 (H3K36) trimethyltransferase, is one of the major genes associated with Wolf-Hirshhorn syndrome, which is characterized by skeletal abnormalities. However, the role of Whsc1 in skeletal development remains unclear. Here, we show that Whsc1 regulates gene expression through Runt-related transcription factor (Runx) 2, a transcription factor central to bone development, and p300, a histone acetyltransferase, to promote bone differentiation. Whsc1 (−/−) embryos exhibited defects in ossification in the occipital bone and sternum. Whsc1 knockdown in pre-osteoblast cells perturbed histone modification patterns in bone-related genes and led to defects in bone differentiation. Whsc1 increased the association of p300 with Runx2, activating the bone-related genes Osteopontin (Opn) and Collagen type Ia (Col1a1), and Whsc1 suppressed the overactivation of these genes via H3K36 trimethylation. Our results suggest that Whsc1 fine-tunes the expression of bone-related genes by acting as a modulator in balancing H3K36 trimethylation and histone acetylation. Our results provide novel insight into the mechanisms by which this histone methyltransferase regulates gene expression.